2014
DOI: 10.1590/s1413-70542014000500009
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol inclusion levels in corn and sunflower silages

Abstract: Due to the seasonal cycle of forage, the use of silage to feed animals provides nutrients throughout the year. However, its quality can be improved with the inclusion of additives and other products. Glycerol is a rich source of energy and present a high efficiency of utilization by animals. The purpose of this work was to evaluate the effect of glycerol inclusion on the chemical and fermentation characteristics of corn and sunflower silages. Two silage sources (maize and sunflower) were used and four levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
6
0
2
Order By: Relevance
“…On the other hand, the crude protein, neutral detergent fiber, acid detergent fiber and ether extract contents decreased. These results are similar to those found by Martins et al (2014) that observed increase of dry matter, non-fiber carbohydrates and total digestible nutrients and reduction of crude protein levels, neutral detergent fiber and acid fiber, due to the addition of glycerin (0, 15, 30 and 45%) in the corn silage.…”
Section: De Bcsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, the crude protein, neutral detergent fiber, acid detergent fiber and ether extract contents decreased. These results are similar to those found by Martins et al (2014) that observed increase of dry matter, non-fiber carbohydrates and total digestible nutrients and reduction of crude protein levels, neutral detergent fiber and acid fiber, due to the addition of glycerin (0, 15, 30 and 45%) in the corn silage.…”
Section: De Bcsupporting
confidence: 91%
“…Martins et al (2014), when assessing the corn and sunflower silages with 0, 15, 30 and 45% of glycerin did not observe differences in pH at the opening of the silages.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The composition of crude glycerin, i.e., mainly non-fibrous carbohydrates, reduced the proportions of NDF and ADF with increasing levels of crude glycerin, which is related to the dilution effect (Table 3). Martins et al (2014) observed reductions by 25.3 and 24.7% of NDF when 450 g kg −1 of DM of glycerin was added to silage produced with corn and sunflower, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…De característica higroscópica e boa palatabilidade pelos ruminantes (Mota et al, 2011), é alternativa para diminuir custos e melhorar o valor nutricional da ração. Ainda, a glicerina possui potencial uso como aditivo, para auxiliar no processo fermentativo e qualidade nutricional em silagens de algumas forrageiras (Martins et al,2014;Rigueira et al, 2017).…”
Section: Introductionunclassified